2006
DOI: 10.1177/154405910608500613
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Trial of Implant-retained Mandibular Overdentures

Abstract: Evidence from randomized clinical trials of implant-retained overdentures is very limited at the present time. The aim of this study was to compare implant-retained mandibular overdentures and conventional complete dentures in a randomized controlled trial (RCT). Our a priori hypothesis was that implant-retained mandibular overdentures would be significantly better than conventional complete dentures. Edentulous patients (n = 118) were randomly allocated to either an Implant Group (n = 62) or a Denture Group (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
110
1
10

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(126 citation statements)
references
References 20 publications
5
110
1
10
Order By: Relevance
“…The fully edentulous condition has negative impacts on oral healtherelated quality of life (OHRQoL) (Szentpetery et al, 2005), including the inability to chew, poor speech, pain, and dissatisfaction with appearance (Walton and MacEntee, 2005). Dental implants that support mandibular prostheses provide significant benefit to edentulous patients (Melas et al, 2001;Awad et al, 2003;Heydecke et al, 2003;Timmerman et al, 2004;Allen et al, 2006;Attard et al, 2006). Allen and McMillian (2003) have shown that patients who requested implants but received conventional dentures reported little satisfaction with dentures and only modest improvements in the quality of life.…”
Section: Introductionmentioning
confidence: 97%
“…The fully edentulous condition has negative impacts on oral healtherelated quality of life (OHRQoL) (Szentpetery et al, 2005), including the inability to chew, poor speech, pain, and dissatisfaction with appearance (Walton and MacEntee, 2005). Dental implants that support mandibular prostheses provide significant benefit to edentulous patients (Melas et al, 2001;Awad et al, 2003;Heydecke et al, 2003;Timmerman et al, 2004;Allen et al, 2006;Attard et al, 2006). Allen and McMillian (2003) have shown that patients who requested implants but received conventional dentures reported little satisfaction with dentures and only modest improvements in the quality of life.…”
Section: Introductionmentioning
confidence: 97%
“…The questionnaire has been applied several times, including in patients with temporomandibular disorders [19, 20], xerostomia [21], burning mouth syndrome [22], tooth agenesis [23] and HIV infection [24, 25]. Clinical trials have also used the OHIP to evaluate implant-supported prostheses [26, 27] and steroidal therapy for oral lichen planus [28]. However, regarding the condition of dentine hypersensitivity (DHS) and OHRQoL (and especially the OHIP), the literature is limited.…”
Section: Introductionmentioning
confidence: 99%
“…Como alternativa, as overdentures são opções reabilitadoras efi cazes, defi nidas como próteses totais ou parciais removíveis que se encaixam sobre raízes residuais ou implantes osseointegrados (4,5).…”
Section: Introductionunclassified